2005
DOI: 10.1152/ajplung.00386.2004
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant phospholipid DPPC downregulates monocyte respiratory burst via modulation of PKC

Abstract: Pulmonary surfactant phospholipids have been shown previously to regulate inflammatory functions of human monocytes. This study was undertaken to delineate the mechanisms by which pulmonary surfactant modulates the respiratory burst in a human monocytic cell line, MonoMac-6 (MM6). Preincubation of MM6 cells with the surfactant preparations Survanta, Curosurf, or Exosurf Neonatal inhibited the oxidative response to either lipopolysaccharide (LPS) and zymosan or phorbol 12-myristate 13-acetate (PMA) by up to 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…Moreover, in this study, the artifi cial surfactant preparations used are devoid of the hydrophilic proteins SP-A and SP-D and contain reduced amounts of the hydrophobic proteins SP-B and SP-C ( 39 ). Furthermore, we show that equivalent antiinfl ammatory activity was produced by the major surfactant phospholipid species, DPPC, at concentrations that have been measured for this lipid in natural surfactant ( 44,45 ). Previous studies, from our laboratories and others, have shown that DPPC has an immunoregulatory role on leukocytes ( 31-36, 40, 46 ).…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, in this study, the artifi cial surfactant preparations used are devoid of the hydrophilic proteins SP-A and SP-D and contain reduced amounts of the hydrophobic proteins SP-B and SP-C ( 39 ). Furthermore, we show that equivalent antiinfl ammatory activity was produced by the major surfactant phospholipid species, DPPC, at concentrations that have been measured for this lipid in natural surfactant ( 44,45 ). Previous studies, from our laboratories and others, have shown that DPPC has an immunoregulatory role on leukocytes ( 31-36, 40, 46 ).…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, plasmalogens, which are antioxidant phospholipids, are also present in higher amounts in PA. Higher plasmalogen content in the tracheal aspirate in preterm infants is associated with a lower risk for developing BPD [75]. Higher amounts of DPPC also offers better anti-inflammatory properties [76], and down-regulates the respiratory burst via modulation of protein kinase C [77]. PA has been approved for use with an initial dose of 200 mg/kg, and 100 mg/kg for subsequent doses, whereas, BE is used at 100 mg/kg, and CA at 105 mg/kg for first and subsequent doses.…”
Section: Animal Derived Surfactantsmentioning
confidence: 99%
“…Some experiments were carried out in the presence of either 5 g/mL superoxide dismutase (SOD), 100 g/mL catalase, 50M diphenyleneiodonium (DPI), 1mM apocynin, or 5M rotenone (Sigma). Human peripheral blood monocytes stimulated with opsonised zymosan 23 were used for comparative purposes.…”
Section: Detection Of Superoxide Using the Chemiluminescent Probe Diomentioning
confidence: 99%